Novel Insight into the in vivo Function of Mast Cell Chymase: Lessons from Knockouts and Inhibitors - Gunnar Pejler (Karger Publishers, 2020)
Mast cells are now recognized as key players in diverse pathologies, but the mechanisms by which they contribute in such settings are only partially understood. Mast cells are packed with secretory granules, and when they undergo degranulation in response to activation the contents of the granules are expelled to the extracellular milieu. Chymases, neutral serine proteases, are the major constituents of the mast cell granules and are hence released in large amounts upon mast cell activation. Following their release, chymases can cleave one or several of a myriad of potential substrates, and the cleavage of many of these could potentially have a profound impact on the respective pathology. Indeed, chymases have recently been implicated in several pathological contexts, in particular through studies using chymase inhibitors and by the use of chymase-deficient animals. In many cases, chymase has been shown to account for mast cell-dependent detrimental effects in the respective conditions and is therefore emerging as a promising drug target. On the other hand, chymase has been shown to have protective roles in other pathological settings. More unexpectedly, chymase has also been shown to control certain homeostatic processes. Here, these findings are reviewed.